Bird diversity in Aketajawe Lolobata National Park - Kurniawan, Andy; Abbas, Nurdiana; Nurdin, Aqshan Shadikin; Baguna, Firlawanti Lestari; Tamnge, Fadila (Foresty Faculty of Hasanuddin University, 2023)
Research on richness and bird species diversity are important for conservation efforts in National Park. Currently, the Aketajawe Lolobata National Park (ALNP) is a habitat patch among industrial areas on Halmahera Island, so that it is important to carry out periodic bird inventories in the national park. Therefore, the need to study the current bird diversity and the status of bird species as a basis for future monitoring and implementation of appropriate conservation measures are important. Bird diversity research needs to be carried out because. Observation plots are placed at primary and secondary forest in Akejawi resort. The research was conducted on January to February 2022. Total observation point is 20 plots. The method was used by point count. The distance between the observation plot is 200 m and the radius of observation is 50 m. The observation were made in the morning (06.00-09.00 am). Repetition of observation on each habitat was carried out 10 times. Data were analyzed by using Shannon-Wiener Index Diversity. Based on findings, There were 345 individuals of 39 species from 19 families inhabited Akejawi Resort. Secondary forest had the highest diversity index when compared to primary forest. This study revealed that there were 9 birds originated from North Maluku and there were 15 species categorized as protected species. The latest data can provide opportunities for further research to reveal patterns of bird distribution and various protection measures due to the loss of forest areas around national parks.